Akibat Hukum Pernikahan Siri Perspektif Hukum Islam - Joni Zulhendra; Dwikornida Dwikornida (Fakultas Hukum Universitas Tamansiswa Padang, 2025)
This article aims to a secret marriage or an unregistered marriage, whether a single marriage or polygamy, is an invalid marriage before positive law. This occurs due to a lack of legal understanding and minimal legal awareness from some people about the importance of registering their marriage. In addition, the conclusion we draw from the factors underlying the occurrence of a secret marriage itself is the high cost of marriage, obstacles during the study period, and a lack of education and understanding of religious teachings. The legal impacts that can arise from a secret marriage include; can cause conflict in the family, for example because it is not approved, interfaith marriage, polygamy and so on, economic and educational impacts, this is usually done by students, the legal impact is that a secret marriage is a violation of the law, social and psychological problems and impacts on religion, for example a secret marriage carried out by a cleric or kyai